NITRATE CONTENT OF TOMATOES, SWEET PEPPERS AND EGGPLANTS - Войцехівський, Володимир; Горбатюк, Світлана; Мулярчук, Оксана; Сметанська, Ірина; Бережняк, Євгеній; Пошкребньов, Вітадій; Ткачук, Світлана (SWorldJournal, 2022)
A comparative study of the content of nitrates in some vegetable products in the winter-spring period, sold in supermarkets in Kyiv, was carried out. During the study, it was found that the concentration of nitrates in the studied vegetables is different.